2018
DOI: 10.1016/j.snb.2018.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic aptamer modified porous reduced graphene oxide/MoS2 based electrodes for viral detection: Application to human papillomavirus (HPV)

Abstract: Next to graphene nanomaterials, molybdenum disulfide (MoS 2 ) offers large surface area that can enhance its biosensing performance. In this work, we investigate the performance of glassy carbon (GC) electrodes modified successively with porous reduced graphene oxide (prGO) and molybdenum sulfide (MoS 2 ) for the sensitive and selective detection of the L1major capsid protein of human papilloma virus (HPV). Owing to the difficulties to perform serological assays and HPV cultures efficiently, tools based on mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 56 publications
(63 reference statements)
1
47
0
Order By: Relevance
“…GO which is one of the most important graphene derivatives and a significant 2DM for various biomedical applications has been studied extensively for its novel antiviral action. Different multiple fabrication and functionalization routes have been adopted to exfoliate GO to enhance its antiviral action on different kind of enveloped and non-enveloped viruses (Sametband et al, 2014;Song et al, 2015;Ye et al, 2015;Chen et al, 2016;Cheng et al, 2017;Yang et al, 2017;Chekin et al, 2018;Du et al, 2018). In all of these cited research articles, modified Hummer's method with complex functionalization and time consuming water based dispersion of GO nanosheets (GO NSs) have been employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GO which is one of the most important graphene derivatives and a significant 2DM for various biomedical applications has been studied extensively for its novel antiviral action. Different multiple fabrication and functionalization routes have been adopted to exfoliate GO to enhance its antiviral action on different kind of enveloped and non-enveloped viruses (Sametband et al, 2014;Song et al, 2015;Ye et al, 2015;Chen et al, 2016;Cheng et al, 2017;Yang et al, 2017;Chekin et al, 2018;Du et al, 2018). In all of these cited research articles, modified Hummer's method with complex functionalization and time consuming water based dispersion of GO nanosheets (GO NSs) have been employed.…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, we have pushed our scientific efforts to knock at the door of 2DMs family to study the synergistic antibacterial and antiviral action of MoS 2 to be compared with that of GO NSs, chosen as a reference material due to its documented bactericide and antiviral action (Sametband et al, 2014;Song et al, 2015;Ye et al, 2015;Chen et al, 2016;Cheng et al, 2017;Yang et al, 2017;Chekin et al, 2018;Du et al, 2018). Thus, here we tested the interactions of MoS 2 and GO NSs with a gram-negative bacterium such as Escherichia.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Chekin et al showed the improvement the biosensing of GCE modified successively with porous reduced graphene oxide (prGO) and molybdenum sulfide (MoS 2 ) for the sensitive and selective detection of the L1‐major capsid protein of HPV16. Using DPV, a detection limit of 1.75 pM could be reached .…”
Section: Methodsmentioning
confidence: 99%
“…Reduced graphene oxide (rGO) and porous reduced graphene oxide (prGO) were prepared based on a study reported by Szunerits. 22,34 Briey, 5 mL of graphene oxide (GO) aqueous solution (1 mg mL À1 ) was sonicated for 3 h at 25 C. Then, hydrazine hydrate solution (32 M, 1 mL) was added to the GO dispersed solution followed by heating in an oil bath for 24 h at 80 C. The product was ltered, washed with water and dried in an oven at 100 C. Next, 5 mg of rGO was sonicated in 5 mL of 30% H 2 O 2 for 30 min and reuxed for 12 h at 60 C. The product was ltered and washed with water. For the preparation of the CS-prGO nanocomposite, 1 mg of prGO was sonicated in 1 mL water for 1 h. Then, 0.5 mL of CS (0.5 mg mL À1 in 1% acetic acid) was added to the prGO suspension solution and sonicated for 30 min at 25 C. The product was ltered, washed with water and stored in a fridge for use.…”
Section: Preparation Of the Porous Reduced Graphene Oxide-chitosan Namentioning
confidence: 99%